Extracellular vesicle-packaged GBP2 from macrophages aggravates sepsis-induced acute lung injury by promoting ferroptosis in pulmonary vascular endothelial cells - Zhixi Li; Yue Bu; Cheng Wang; Yongjing Yu; Lei Han; Chang Liu; Guangmin Chen; Chenglong Li; Yan Zhang; Hang Cao; Zhaoxue Ma; Ziyong Yue (Redox Biology)
Macrophages play a critical role in the development of sepsis-induced acute lung injury (si-ALI), with extracellular vesicles (EVs) acting as crucial mediators. However, the effects and mechanisms of macrophage-derived EVs on si-ALI remain unclear. This study demonstrated that macrophage-derived EVs induce endothelial ferroptosis and barrier disruption during sepsis. Through proteomic sequencing and reanalysis of transcriptomic and single-cell sequencing data, guanylate-binding protein 2 (GBP2) was identified as a key EV molecule. Elevated GBP2 expression was observed in EVs and monocytes from the peripheral blood of sepsis patients, in LPS-stimulated THP-1 and RAW264.7 cells and their secreted EVs, and in macrophages within the lungs of CLP mice. Additionally, GBP2 expression in EVs showed a positive correlation with vascular barrier injury biomarkers, including ANGPT2, Syndecan-1, and sTM. Modulating GBP2 levels in macrophage-derived EVs affected EV-induced ferroptosis in endothelial cells. The mechanism by which GBP2 binds directly to OTUD5 and promotes GPX4 ubiquitination was elucidated using RNA interference, adeno-associated virus transfection, and endothelial-specific Gpx4 knockout mice. A high-throughput screening of small-molecule compounds targeting GBP2 was conducted. Molecular docking, molecular dynamics simulations, and cellular thermal shift assays further confirmed that Plantainoside D (PD) has a potent binding affinity for GBP2. PD treatment inhibited the interaction between GBP2 and OTUD5, leading to a reduction in GPX4 ubiquitination. Further research revealed that PD treatment enhanced the pulmonary protective effects of GBP2 inhibition. In conclusion, this study explored the role of EV-mediated signaling between macrophages and pulmonary vascular endothelial cells in si-ALI, highlighting the GBP2-OTUD5-GPX4 axis as a driver of endothelial ferroptosis and lung injury. Targeting this signaling axis presents a potential therapeutic strategy for si-ALI.